Multiwavelength Laser With Adjustable Ultranarrow Wavelength Spacing - C. H. Chang; P. C. Peng; R. K. Shiu; J. J. Jhang; Y. H. Chen; T. L. Chang (IEEE Photonics Journal, 2016)
This paper investigates the use of a dual wavelength laser source, a frequency shifter, an erbium-doped fiber amplifier, and an optical filter to compose a multiwavelength fiber laser (MWFL) with an ultranarrow wavelength spacing. The frequency shifter can be achieved by modulating an optical carrier and an electrical sinusoidal signal in an optical single-sideband modulation format. The detuning range of the frequency shifting can be controlled by the applied electrical sinusoidal signal, and an MWFL with ultranarrow wavelength spacing can be achieved. Experimental results prove that 144 stable optical carriers can be generated simultaneously with a 10-GHz wavelength spacing, > 15-dB optical signal-to-noise ratio, and < 0.83-dB maximum peak power variation, if a dual wavelength laser source is fed into the MWFL and the frequency of the electrical sinusoidal signal is set to 10 GHz. Results prove that the ability of the proposed scheme practically and efficiently assist the progress of optical systems.